2021
DOI: 10.1093/mnras/stab942
|View full text |Cite
|
Sign up to set email alerts
|

Using Pantheon and DES supernova, baryon acoustic oscillation, and Hubble parameter data to constrain the Hubble constant, dark energy dynamics, and spatial curvature

Abstract: We use Pantheon Type Ia supernova (SN Ia) apparent magnitude, DES-3yr binned SN Ia apparent magnitude, Hubble parameter, and baryon acoustic oscillation measurements to constrain six spatially flat and non-flat cosmological models. These sets of data provide mutually consistent cosmological constraints in the six cosmological models we study. A joint analysis of these data sets provides model-independent estimates of the Hubble constant, $H_0=68.8\pm 1.8\ \rm {km \ s^{-1} \ Mpc^{-1}}$, and the non-relativistic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 106 publications
3
47
1
Order By: Relevance
“…The prior range of the QSO nuisance parameter lm is not bounded. The computation of the likelihood functions of H(z), BAO, H iiG, and QSO data are described in Cao et al (2020) and Cao et al (2021a), whereas that of the likelihood functions of SN Ia measurements can be found in Cao et al (2021b). One can also find the definitions of the Akaike Information Criterion (AIC) and the Bayesian Information Criterion (BIC) in those papers.…”
Section: Data Analysis Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The prior range of the QSO nuisance parameter lm is not bounded. The computation of the likelihood functions of H(z), BAO, H iiG, and QSO data are described in Cao et al (2020) and Cao et al (2021a), whereas that of the likelihood functions of SN Ia measurements can be found in Cao et al (2021b). One can also find the definitions of the Akaike Information Criterion (AIC) and the Bayesian Information Criterion (BIC) in those papers.…”
Section: Data Analysis Methodologymentioning
confidence: 99%
“…The following summary values are obtained with the same method used inCao et al (2021b), where we take the summary central value to be the mean of the two of six central-most values. As for the uncertainty, we call the difference between the two central-most values twice the systematic uncertainty and the average of the two central-most error bars the statistical uncertainty, and compute the summary error bar as the quadrature sum of the two uncertainties.MNRAS 000, 1-13 (2021)…”
mentioning
confidence: 99%
“…Using the latest BAO data, including the eBOSS DR16 measurements [34], and a prior on Ω m h 2 based on the Planck 2018 best fit in a ΛCDM model, reference [53] finds H 0 = 69.6 ± 1.8 km s −1 Mpc −1 at 68% CL. Considering Pantheon SNIa apparent magnitude + DES-3yr binned SNIa apparent magnitude + H(z) + BAO in reference [54] the authors find H 0 = 68.8 ± 1.8 km s −1 Mpc −1 at 68% CL. In reference [55] the authors apply the inverse distance ladder to fit a parametric form of H(z) to BAO and SNIa data, using priors on the sound horizon at the drag epoch r d from Planck, obtaining H 0 = 68.42 ± 0.88 km s −1 Mpc −1 at 68% CL, and from WMAP, obtaining H 0 = 67.9 ± 1.0 km s −1 Mpc −1 at 68% CL.…”
Section: Earlymentioning
confidence: 99%
“…There are a handful of astronomical data sets in this range that are starting to be used in cosmology. These data sets include HII starburst galaxy observations reaching to ∼ 2.4 (Mania & Ratra 2012;Chávez et al 2014;González-Morán et al 2019Cao et al 2020Cao et al , 2021aJohnson et al 2021), quasar (QSO) angular size observations reaching to ∼ 2.7 (Cao et al 2017;Ryan et al 2019;Cao et al 2020Cao et al , 2021bZheng et al 2021;Lian et al 2021), and gamma-ray burst observations reaching to ∼ 8.2 (Amati et al 2008(Amati et al , 2019Samushia & Ratra 2010;Wang et al 2016Wang et al , 2021Demianski et al 2019;Fana Dirirsa et al 2019;Khadka & Ratra 2020c;Khadka et al 2021a).…”
Section: Introductionmentioning
confidence: 99%